Syntactic Category Changing in Syntax: Evidence from Finnish Participle Constructions - Koskinen, Päivi (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1999)
ABSTRACTIn most languages there are lexical elements that manifest morpho-syntactic properties associated with more than one lexical category. I examine here a group of Finnish participle constructions that manifest such categorial inconsistencies. Those forms are analyzed as containing a hybrid category: the lexical feature [Adjectival Reference] accounts for their adjectival qualities and seemingly nominal morphology, while a functional feature [Temporal Reference] (= Tense) explains their verbal and temporal characteristics. Consequently, I argue that changes in syntactic category take place not only through morphological derivation, but also within the syntactic component. This is possible under a view of morphological derivation as vocabulary insertion based on the syntactic feature matrices that surface at the end of the computational component.